If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 = z Solving 12 = z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-1z' to each side of the equation. 12 + -1z = z + -1z Combine like terms: z + -1z = 0 12 + -1z = 0 Add '-12' to each side of the equation. 12 + -12 + -1z = 0 + -12 Combine like terms: 12 + -12 = 0 0 + -1z = 0 + -12 -1z = 0 + -12 Combine like terms: 0 + -12 = -12 -1z = -12 Divide each side by '-1'. z = 12 Simplifying z = 12
| (4+u)(5u-2)=0 | | 5x-20=3x+15 | | 9y^2+66y+122=0 | | x*.3=2.5 | | 10a+3(a+2)= | | (2v-7)(5-v)=0 | | 5(x+7)+4x^2=(x+5)(x+7) | | 3sin(x)+2cos(x)=0 | | 10x+[2+8x]=4 | | 4x^3-2xy= | | 2.5=11.50 | | 28=8+2x | | -2t-5= | | -53+12X=115 | | 9x-2[x+4]=34 | | Ln(4x-7)=ln(x+5) | | -63=-27-3X | | y+5.8=1.34 | | x+(-12)=112 | | (h^3-2h)+(3h^2+4h)-2h^3= | | 4y=6x-4 | | 100-5p=-20+7p | | 127=-11x-71 | | -8(y+1)+1=-8y-6 | | x(31-5-x)=10-3x | | 147=63+6x | | 5x-7=2x+7 | | 10m-17m-25m+21m+m=16 | | -5x+23=32 | | 7(x-1)=5(x-15) | | ln(8x-7)=2 | | 8x+44=100 |